Firearm screening in pediatric patients - Kandeepan, Aarani; Lee, Jessica; Bagdure, Dayanand; Garber, Nan; Day, Jenni; Holloway, Adrian; Lichenstein, Richard; Slattery, Joseph; Wolfe, Alexa; Wadsworth, Jenna; Moss, Julianne; Davie, Nicole; et al. (Frontiers in Pediatrics, 2024)
In the United States, firearm-related injuries are the leading cause of death among children and adolescents 1-19 years of age. Although many pediatricians believe addressing firearm safety is important and have guidance from organizations like the American Academy of Pediatrics, few routinely screen and counsel on firearm safety. The goal of this project was to screen all patients presenting to the pediatric emergency department, pediatric floor, and pediatric intensive care unit for the presence of firearms in the home, firearm storage practices, and whether they had previously received any firearm counseling by medical professionals. A13-item survey was administered to each participant. Items included demographic information, willingness to answer questions about firearms, practice of asking questions about firearms, previous counseling from medical professionals about the presence of firearms in the home and the presence of firearm in their personal home as well as storage practices. A total of 200 parents responded to the survey. Of those that responded to the survey, (85.5%) did not have a firearm in the home and 28 (14%) did have a firearm in the home. 75% (n=21) had never had a medical provider discuss firearm safety with them. 100% had never been asked by another parent about the presence of a firearm in their home when a child came over for a playdate. 39% (n=11) of parents with a firearm in the home had asked other parents whether they have a firearm in the home where their child goes to play. Findings from our study highlight a significant lack of screening of our pediatric patients both in the inpatient and outpatient settings, with the majority reporting that they had never been asked by a medical provider about firearm safety. In addition, three quarters of parents with a firearm in the home reported that they did not mind answering questions about firearms yet none had been asked by other parents about firearms. Thus, although firearm possession and safety is considered to be a sensitive topic, many parents are willing to discuss it with their health care providers and other parents.